Convention of the settlement of investment disputes between States and nationals of other States (ICSID) - García Calderón Moreyra, Gonzalo (2020)
The article explains the operation of the International Center for Settlement of Investment Disputes between States and nationals of other States, taking into account the importance of this center in the resolution of conflicts in Peru today.